Competing twinning mechanisms in body-centered cubic metallic nanowires. (1st March 2016) - Shi, Zhe; Singh, Chandra Veer
Abstract: Twinning in body-centered cubic metals is typically attributed to glide of 1/6 < 111 > dislocations originated from material defects. Here we report an alternative mechanism for twin formation in body-centered cubic nanowires using molecular dynamics simulations. In this mechanism, twinning is triggered by dissociation of the 1/6 < 111 > dislocation into two 1/12 < 111 > partials gliding on adjacent 211 planes. By comparing the generalized stacking fault energies of the two competing twin boundary configurations in five different BCC crystals, the propensity of a particular mechanism to occur is evaluated. The fundamental insight gained from this study will help engineer nanoscale materials with novel mechanical properties. Graphical abstract: